The Road to Ivanpah - Jay M. Price (Symphony in the Flint Hills, 2014)
Sometimes there are places we want to visit just because they are there. For me, one of those was Ivanpah, pretty much just a place name in Salem Township in west central Greenwood County. I had come across the name when doing research on oil development in Kansas, and it just intrigued me.
Keywords: Ivanpah; road; exploration; town; small; adventure; clear water; Native Americans; Indians; Ivanpah Creek; peace